Human Papillomavirus and Coronary Artery Disease in Climacteric Women: Is There an Association? - Luciane Maria Oliveira Brito; Haissa Oliveira Brito; Rita da Graça Carvalhal Frazão Corrêa; Clariano Pires de Oliveira Neto; Joyce Pinheiro Leal Costa; Sally Cristina Moutinho Monteiro; Flávia Castello Branco Vidal; Maria do Desterro Soares Brandão Nascimento; José Albuquerque de Figueiredo Neto; Rui Miguel Gil da Costa; Leonardo Victor Galvão-Moreira; Ismael Dale Cotrim Guerreiro da Silva (The Scientific World Journal)
Background. Cardiovascular diseases are leading causes of death worldwide. Recent studies suggest that infection by some viruses, including the human papillomavirus (HPV), may increase the risk of developing atheromatous lesions on coronary arteries. However, there is a lack of data regarding the possible association between HPV infection and coronary artery disease (CAD) in women. Objective. To investigate whether HPV infection is associated with the occurrence of CAD among climacteric women. Methods. The presence of CAD and cervical HPV DNA was investigated in 52 climacteric women. Social and demographic variables and metabolic profiles were also investigated. Results. Among 27 women with CAD, 16 were positive for HPV, whereas 11 were negative. The presence of cervical HPV was strongly associated with CAD, after adjusting for demographic variables, health and sexual behaviors, comorbidities, and known cardiovascular risk factors. HPV-positive women showed a greater likelihood of having CAD (odds ratio [OR] = 3.74; 95% confidence interval [CI]: 1.16 to 11.96) as compared with HPV-negative women, particularly those infected with high-risk HPV types (OR = 4.90; 95% CI: 1.26 to 19.08). Conclusion. These results support the hypothesis that HPV infection might be associated with CAD among climacteric women, though further studies are needed to investigate the mechanisms involved.